Nutritional review of the methodology applied in sports supplementation research - Cantero, Leticia; Conde-Pipo, Javier; Jimenez-Casquet, Maria Jose; Latorre, Jose Antonio; Gimenez-Blasi, Nuria; Martinez-Bebia, Manuel; Bach-Faig, Anna; Olea-Serrano, Fatima; Miguel Mariscal-Arcas (Progress in Nutrition, 2022)
Both high-performance athletes and amateurs resort to taking supplements in order to improve their performance and/or their health. Many of them do not know the effects of these and take them without a professional supervision. The aim is to know the population who is studied by other different studies related to supplementation and improvement of sports performance and the nutritional method used in these cases.Systematic bibliographic research (March-May2021) was carried out in MEDLINE, with Boolean operators (((((caffeine[MeSH Major Topic]) OR (creatine[MeSH Major Topic])) OR (nitrate[MeSH Major Topic])) OR (sodium bicarbonate[MeSH Major Topic])) AND (dietary supplement[MeSH Terms])) AND (athletic performance[MeSH Terms]). 17 articles were included.Mean participants of these studies were 16.8subjects, which corresponds to a small sample. Only two studies were conducted to women. Several others were based on people who are not considered high-performance. In most of the selected studies, there is no a nutritional assessment, dietary record or follow-up of the subjects’ diet before and during the intervention, and this is a limitation.In order to reach accurate conclusions about supplementation and optimization of sports performance, it is necessary to know the nutritional and hydration status, supplementation habits and lifestyle of the participants in these trials are.